Photocatalytic activity of colloidal Bi-Si-based nanoparticles prepared by laser synthesis in liquid - Golubovskaya, Aleksandra G.; Goncharova, Darya A.; Fakhrutdinova, Elena D.; Kharlamova, Tamara S.; Vodyankina, Olga V.; Svetlichnyi, Valerii A. (Materials Chemistry and Physics)
A combination of laser ablation and laser irradiation by focused laser beam in liquid is used to prepare the Bi- and Si-based nanocolloids in water in a Bi:Si molar ratio of 12:1. The composition, structure, morphology, and optical properties of the obtained nanostructures are studied. The synthesized composite nanostructures are shown to consist mainly of bismuth oxycarbonate Bi2(CO3)O2 and bismuth silicate Bi12SiO20. The materials are tested in the decomposition of the model dye rhodamine B, including the stability of the catalyst and the opportunity of its regeneration by laser irradiation as well as in phenol decomposition when excited by LED with a wavelength of 375 nm. The opportunity to use the Bi-Si-based colloidal nanostructures for the selective photooxidation of 5-(hydroxymethyl)furfural is considered.